260 Comparison of Patient Satisfaction and Outcomes of Day Case Mastectomy Versus Inpatient Model, Using a Validated Questionnaire. (28th February 2022) - Ramasamy, S.; Fazel, M.; Patel, G.
Abstract: Introduction: Many women undergoing simple mastectomy have an overnight hospital stay. Offering a day case procedure for simple mastectomy has the potential to improve outcomes in terms of patient safety, feasibility, and reduction in associated costs. We aimed to study the proportion of day case mastectomies over a 2-year period and assessed relative readmission and complication rates alongside patient reported outcome measures (PROMs). Following this, we wanted to analyse whether a day case procedure should be routinely offered. Method: A retrospective audit was conducted on all patients undergoing a simple mastectomy. Data were collected from patient and pathology records. PROMs were obtained via telephone conversation using the validated BREAST-Q survey. Patient demographics, reason for mastectomy and readmission for complications were all assessed. Results: Out of the 202 patients analysed, over 75% had an overnight stay. The most common complications for both groups of patients were readmission due to infection and haematoma evacuation, with similar rates across the two (p = 0.26, p = 0.69). Data from PROMs also suggested that patients had similar outcome and satisfaction levels (p = 0.27). Conclusions: The result from this study shows that it is safe as well as acceptable to patients to offer simple mastectomies as a day case procedure. This has become more important since COVID-19 reduced inpatient theatre capacity, and it is anticipated that these outcomes will allow a routine day case mastectomy pathway to be established even when normal operations recommence as encouraged by the association of day case surgery.